The future of green tourism in Bali: Challenges and opportunities - Ni Nyoman Sri Astuti; Putu Tika Virginiya; Ni Ketut Bagiastuti; Elvira Septevany (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This research examines the future of green tourism in Bali, analyzing the challenges and opportunities facing the island in its sustainable tourism development efforts. The research adopts a multi-method qualitative approach, including a systematic literature review using the PRISMA method, in-depth semi-structured interviews, and participatory observation. Data were collected from key stakeholders in Bali's tourism industry, including experienced tourism operators, government officials, environmental experts, and community leaders representatives. Respondents were selected using purposive sampling, with the criteria of having a minimum of five years of experience in Bali's tourism industry or related fields. Their role was to provide insights into the current state of green tourism in Bali, challenges faced, and potential development opportunities. Key findings revealed significant challenges such as environmental damage from mass tourism, inadequate waste management, threats to biodiversity, cultural exploitation, and economic inequality. Nonetheless, Bali also shows great potential for green tourism development, including supportive government policies, community engagement opportunities, technological advances, and the growing global demand for sustainable tourism experiences. This research proposes a comprehensive strategy to boost green tourism in Bali, emphasizing stakeholder collaboration, sustainable tourism standards, eco-friendly infrastructure improvements, and awareness-raising campaigns.